Evolution of Peruvian Constitutionalism - Carpio Marcos, Edgar (2016)
This paper is based on the idea that the constitutional evolution of Peru designates a “process” in which happend gradually was consolidated an alteration in the structure of political and social relations that developed in our territory as a result of his inflection , or regulation based on constitutional texts or legal documents that served as such.